Anti-cancer effect of a new monoorganotin Schiff base complex, [N-(3,5-Oxidobenzylidene)-4-chlorobenzyhdrazidato] (0-methylbenzyl) aquatin (IV) chloride on human breast cancer cells and mammospheres / Somayeh Fani - Somayeh, Fani (2017)
Undesirable side effects of current cancer chemotherapeutic and multidrug resistance lead to an increasing interest toward investigating new anticancer agents, including synthetic compounds, with limited toxicity to normal tissue and less multidrug resistance of tumor cells. The organotin schiff base complexes have been investigated for anticancer studies. The activity of a new monoorganotin schiff base complex, [N-(3,5-dichloro-2-oxidobenzylidene)-4-chlorobenzyhydrazidato](o-methylbenzyl)aquatin (IV) chloride (C1), was investigated on human breast cancer (BC) cells and on mammospheres derived from BC cells. The acute toxicity experiment with compound C1 revealed no toxicity effects on rats. Compound C1 was exposed to several human cancer cell lines including breast adenocarcinoma cell lines, MCF-7 and MDA-MB-231, ovarian adenocarcinoma cell lines, Skov3 and Caov3, and prostate cancer cell line, PC3, in order to examine its cytotoxic effect on different human cancer cell lines. Human breast cell MCF10A and human hepatic cell line, WRL-68, were used as non-cancerous cell lines control. Subsequently, we focused in this study on MCF-7 and MDA-MB-231 cell lines to detect possible underlying mechanism such as apoptosis, involvement of compound C1. MTT assay revealed the strongest cytotoxicity of compound C1 against MCF-7 and MDA-MB-231 cells with the IC50 value of 2.5±0.50 μg/mL (0.0040 μΜ) after 48 hours treatment in comparison to ovary and prostate cancer cells. The IC50 values were 28±0.40 μg/mL (0.045 μΜ) in MCF10A cells and 38±0.38 μg/mL (0.061 μΜ) in WRL-68 cells after 48 hours. Cisplatin was used as a positive control drug with IC50 values of 1±0.45 μg/mL (0.0016 μΜ) and 0.9±0.49 μg/mL (0.0014 μΜ) against MCF-7 and MDA-MB-231 cells, respectively. A significant increase of LDH release in MCF-7 and MDA-MB-231 treated cells was observed via fluorescence analysis. Luminescence analysis showed a significant generation of intracellular reactive oxygen species (ROS) after treatment with compound C1 on MCF-7 and MDA-MB-231 cells. iv The morphological changes of necrosis, early and late apoptosis stages were observed in MCF-7 and MDA-MB-231 treated cells after staining with AOPI. The characteristic of apoptosis and DNA fragmentation, were also observed in MCF-7 and MDA-MB-231 treated cells. Real time PCR and western blotting showed downregulation of Bcl2, HSP70 and upregulation of Bax, in MCF-7 and MDA-MB-231 cells because of cytochrome c release from the mitochondria to the cytosol. Compound C1 elicited significant (P < 0.05) G0/G1 phase arrest in both breast cancer cell lines. The cytochrome c release caused caspase-9 activation, which then activated caspase-7 which resulted in apoptotic changes. Compound C1 has significantly (P < 0.05) reduced the aldehyde dehydrogenase-positive cell population, the size and number of MCF-7 and MDA-MB-231 mammospheres in primary, secondary, and tertiary culture in vitro. Compound C1 also downregulated the Wnt/β-catenin self-renewal pathway significantly (P < 0.05) in both breast cancer cell lines. Results obtained from the present study revealed that the compound C1 possess potential cytotoxic effects against human breast cancer MCF-7 and MDA-MB-231cells. Compound C1 may lead to the finding of more cancer management strategies by reducing cancer resistance and recurrence via its cytotoxic effect on mammospheres.